How are markets made? - Patrik Aspers (Max Planck Institute for the Study of Societies, 2009)
The purpose of this paper is to analyze the making of markets. The paper identifies two ideal-typical processes in which markets are made - organized making and spontaneous making - which are often combined in reality. Organized making is defined as a process in which at least two actors come together and decide on the order of the market. There are two ways of organized making of markets, called 'state-governed market making' and 'self-governed market making.' Spontaneous making is defined as a process in which the market is an unintended result of actors' activities. The attention sociologists have paid to the issue of market making has been directed largely at organized market making. This paper develops a sociological approach that integrates both spontaneous and organized market making, and identifies three phases of market making. This involves a discussion of empirical cases, and seven hypotheses are presented that make predictions for the two types of market making. The paper provides theoretical tools for studying the making of markets in history, as well as in our own time. Finally, a number of conditions are presented that must be in place if there is to be a market. – – Dieses Working Paper analysiert, wie Märkte geschaffen werden. Hierzu werden zwei idealtypische Prozesse identifiziert, die in der Realität oft miteinander gekoppelt sind: die organisierte und die spontane Schaffung von Märkten. Die organisierte Schaffung wird als ein Prozess definiert, in dem mindestens zwei Akteure zusammenkommen und über die Ordnung eines Marktes entscheiden. Hierbei wird zwischen der 'staatlich regulierten' und 'selbstgesteuerten' Schaffung von Märkten unterschieden. Die spontane Schaffung wird als ein Prozess definiert, in dem ein Markt als unbeabsichtigtes Ergebnis aus dem Handeln von Akteuren hervorgeht. Bis zum gegenwärtigen Zeitpunkt wurde vor allem die organisierte Schaffung von Märkten untersucht. Dieses Papier entwickelt einen soziologischen Ansatz, der sowohl die spontane als auch die organisierte Schaffung umfasst und drei Phasen des Schaffungsprozesses identifiziert. Dabei werden empirische Fälle diskutiert und sieben Hypothesen aufgestellt, die Prognosen zu den beiden Arten der Schaffung von Märkten liefern. Darüber hinaus werden theoretische Instrumente vorgestellt, mit denen sich die Schaffung von Märkten im Lauf der Geschichte und in der Gegenwart untersuchen lässt, sowie schließlich die Voraussetzungen, die erfüllt sein müssen, damit ein Markt zustande kommen kann.
Keywords: 300; Markt; Wirtschaftssoziologie; Theorie